DEVELOPING A BASIC UNDERSTANDING ABOUT SPOOF ATTACKS. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This paper provides an overview of spoofing and helps readers gain a better knowledge ofthe different types of assaults that are feasible, as well as how to protect themselves fromsuch attacks. Spoofing attacks, in which an attacker replaces the original source address inthe header with a new one in order to conceal their identity and location, continue to be oneof the most devastating types of cyber-attacks. One of the most common spoofing attacks thatusers today are subjected to is the email spoofing attack, in which the spoofer obtainsinformation about the email user before attacking through a fake email sender with fakemessages and viruses to attack the user's system, mail list, and other resources, resulting ingreater destruction to the email user who unknowingly opened and reacted to that mail.